KEKOHESIAN WACANA STAND UP COMEDY DI KOMPAS TV - Zumrotul Ilmiyah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
The research method in this research is descriptive qualitative. The research object is the cohesion discourse in Stand up Comedy performed by Dodit Mulyanto on Kompas TV. The technique used to collect the research data is by listening, SBLC, recording, noting, and taking transcription technique. The data then analyzed by using descriptive qualitative method. The result shows that the cohesion aspects give much contribution in improving the whole Stand up Comedy discourse. The cohesion aspect in Stand up Comedy are grammatical cohesion (Pronominal, substitution, ellipsis, and conjunction) and lexical cohesion (Antonym, hyponym, collocation, synonym, and repetition). However the aspect of grammatical conjunction much dominates in this research.